Effect of Fuzzy Logic Based-Skyhook Policy with Particle Swarm Optimization for Semi-Active Ride Comfort - Hussin Ab Talib, Mat; Zaurah Mat Darus, Intan; Mohd Samin, Pakharuddin (International Journal of Engineering and Technology, 2018)
This paper presents the effect of the fuzzy logic based-skyhook policy tuned using particle swarm optimization (FLSP-PSO) for semi-active ride comfort of quarter vehicle model. Spencer model was used to represent the magnetorheological damper model and its behavior was investigated in the form of force-displacement and force-velocity characteristics. The fuzzy logic control adopted with the skyhook policy based on Sugeno-type fuzzy was used to enhance the ride performance. An intelligent evolutionary algorithm known as the particle swarm optimization was also adapted in the proposed controller to compute the fuzzy gain scaling. The performance of the FLSP-PSO controller is compared to other controller responses. The effect of the PSO techniques to optimize the FLPS parameters gives a better performance and able to improve the vehicle ride comfort than its counterparts.Â Â